Os efeitos climáticos do setor da soja no comércio entre Brasil e a União Europeia: uma abordagem através do modelo gravitacional - Flach, Júlia Elisa (2021)
This study is intended to analyze if the increase in soybean trade flows between Brazil and the EU has contributed to a greater deterioration of the environment. In particular, with regard to the increase in CO2 emissions, in the period from 1990 to 2017. For therefore, the methodology chosen in the development of the study was the Gravitational Model. The model applied in the study, based on the Bergstrand Equation (1985), made use of traditional variables, such as the size of economies, measured through GDP and geographical distance. In addition, considering the study by Folfas et al. (2011), variables related to CO2 emissions from agricultural production in Brazil and the EU, the exchange rate and the similarity index of the products in the units in question were added to the model. Empirically, after carrying out statistical tests, the model was estimated using panel data via Pooled, where the dependent variable is the export of Brazilian soybean to the European community. The estimates found indicate that the emissions from Brazilian soybean production and the volume of exports have a positive relationship. That is, in Brazil, agricultural exploitation in soybean production has not reached the level indicated by the Kuznets Curve yet, in which production is optimized and emissions are reduced.